2021
DOI: 10.1074/jbc.ra120.016234
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial CAR design improves target restriction

Abstract: CAR T cells targeting the B-lymphocyte antigen CD19 have led to remarkable clinical results in B-cell leukemia and lymphoma, but eliminate all B-lineage cells, leading to increased susceptibility to severe infections. As malignant B cells will express either immunoglobulin (Ig) light chain κ or λ, we designed a second-generation CAR targeting Igκ, IGK CAR. This construct demonstrated high target specificity, but displayed reduced efficacy in the presence of serum IgG.  Since CD19 CAR is insensitive to serum Ig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…In addition, ECAR measures the rate of extracellular acidification, which mainly comes from the accumulation of lactic acid in the medium (glycolytic pathway) [64]. Among the studies reported, some used the Seahorse technology to explore the influence of CAR signaling tails (4-1BB vs. CD28) [49,65], while others focused on comparing CARs with either different designs or targets [52,[66][67][68][69], the additional secretory functions [53,70], the combination with PD-1/PD-L1 blockage [71], the polarization of the T cells [53,72], or the influence of co-expressing enzymes alongside the CARs in T cells [73,74]. The second injection of Oligomycin, an ATP synthase inhibitor, permits, through the measurement of ECAR, assessment of the maximum glycolytic capacity.…”
Section: Study Of Metabolism In Car T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ECAR measures the rate of extracellular acidification, which mainly comes from the accumulation of lactic acid in the medium (glycolytic pathway) [64]. Among the studies reported, some used the Seahorse technology to explore the influence of CAR signaling tails (4-1BB vs. CD28) [49,65], while others focused on comparing CARs with either different designs or targets [52,[66][67][68][69], the additional secretory functions [53,70], the combination with PD-1/PD-L1 blockage [71], the polarization of the T cells [53,72], or the influence of co-expressing enzymes alongside the CARs in T cells [73,74]. The second injection of Oligomycin, an ATP synthase inhibitor, permits, through the measurement of ECAR, assessment of the maximum glycolytic capacity.…”
Section: Study Of Metabolism In Car T Cellsmentioning
confidence: 99%
“…In particular, they performed RNA sequencing and showed that their CD19-sPD1 CAR T cells were less differentiated and less exhausted and activated less glycolytic pathway-related genes. We have recently presented an approach to improving the efficacy of CD19 CAR T cells by combining CD19 CAR with an anti-IgKappa (IGK) CAR, called Kz19BB [66]. With this combinatorial CAR design, we showed that we could keep the specificity of IGK CAR while attenuating its serum sensitivity.…”
Section: Effect Of the Combination Of Car T Cells And Combinatorial D...mentioning
confidence: 99%
“…It is noteworthy that this platform eliminates the need for cumbersome transport and washing procedures, which are usually inevitable in downstream cell spheroid analysis [ 31 ], as washing and staining after co-culture of immune cells and tumor spheroids are usually required. Unlike other devices, 3DHSP does not require both expensive fluorescent staining and washing steps for spheroid size measurement [ 2 , 24 , 32 ] (Table 1 ). In addition, this platform enables real-time visualization of HER2-CAR T cells infiltrating into the tumor spheroid.…”
Section: Resultsmentioning
confidence: 99%
“…Frontiers in Bioengineering and Biotechnology frontiersin.org (Köksal et al, 2019;Köksal et al, 2020;Pierre et al, 2021). The T cells were kept at a concentration of 1 × 10 6 cells/mL throughout the culture period, with fresh medium added every second day.…”
Section: Figurementioning
confidence: 99%